Dynamic Crack Initiation Toughness of Shale under Impact Loading - Guoliang Yang; Xuguang Li; Jingjiu Bi; Shuaijie Cheng (Energies, 2019)
The impact loading of a notched semi-circular bend (NSCB) specimen of outcrop shale in Changning Sichuan was carried out using a split Hopkinson pressure bar (SHPB) to study the effect of shale bedding on the dynamic crack initiation toughness. Three loading configurations were tested: Crack-divider, Crack-splitter and Crack-arrester loading. Bedding plane has a significant effect on the crack initiation of shale. Under the Crack-divider and Crack-splitter modes, shale had lower dynamic crack initiation toughness. The dynamic crack initiation toughness of the shale was affected by the loading rate for all three loading configurations. The correlation between loading rate and dynamic crack initiation toughness was most significant for the Crack-arrester mode, while the Crack-splitter mode was the weakest. When loading was carried out on Crack-arrester, the bedding plane could change the direction of crack growth. In the Crack-splitter mode, only a small impact energy was needed to achieve effective expansion of a crack. The research results provide a theoretical basis for shale cracking.